IMPLEMENTASI KEBIJAKAN SEKOLAH GRATIS DI SMP JUARA KOTA PEKANBARU - Rian Mahilda; Azhar Azhar; Daviq Chairilsyah (Universitas Riau, 2018)
This study aimed to obtain information on the implementation of the policy offree school for underprivileged students in terms of economics in the Champions Junior HighSchool Pekanbaru. Sub focus in this study were: (1) Understanding the implementation of freeschool policy in the Champions Junior High School Pekanbaru. (2) What were the Objectives,requirements and budget in the the implementation of free school policy are implemented. (3)The supporting factors of the implementation of free school policy in the Champions JuniorHigh School Pekanbaru. (4) The obstacles that arise in the implementation of free schoolpolicy. (5) How to overcoming the obstacles to the implementation of free policy. This studyused a qualitative approach. Data collection techniques in this research were through observation,interviews, documentation and triangulation. Data were analyzed by using analysis model Millesand Hubberman. Based on the results of this study concluded that: (1) The Implementation offree school policy in the Champions Junior High School is already match with the expectation(2) Input and output are in accordance with Implementation of free school policy in the ChampionsJunior High School is received underprivileged students in economics, the Champions JuniorHigh School students have get many achievements both in academic and non-academic, andthe Champions Junior High School graduates able to compete go to Senior high school, MA,and SMK both state and private. (3) Supporting factors are the Zakat house Foundations,Pekanbaru city government, the school, and the parents of student. (4) The obstacles that arisewas delay disbursement of BOS funds, to convince the students and parents about the importanceof education, there are still teachers who teach subjects other than their science subject, andstill lack of facilities and infrastructure to support teaching and learning process. (5) Problemssolving of the implementation of free school policy has been pursued its complete, although it isnot maximized overall.